Adherence to DASH dietary pattern is inversely associated with osteoarthritis in Americans. (17th August 2020) - Zhang, Yurong; Francis, Ellen C.; Xia, Tong; Kemper, Karen; Williams, Joel; Chen, Liwei
Abstract: Osteoarthritis (OA) is one of the most common diseases that cause disability among older adults. The objective of this study was to assess the association between adherence to the Dietary Approaches to Stop Hypertension (DASH) and OA in American adults. This study included adults (≥ aged 20 years) who participated in the National Health and Examination Survey (NHANES) 2007–2016 in the United States. Adherence to the DASH score was calculated from 8 food groups. Higher scores indicate better adherence to the DASH dietary pattern. Among the 21, 901 participants included in this study, 10.26% reported having OA. Results of our multivariable logistic regression indicated a statistically significant inverse association between DASH score tertiles and OA. The adjusted ORs (95% CI) were 1.00 (ref), 0.89 (0.72; 1.10), and 0.78 (0.60; 1.00) across increasing DASH score tertiles ( P for trend = 0.045). In this representative sample of American adults, greater adherence to the DASH dietary pattern was associated with lower likelihood of having OA. Graphical Abstract: